1986
DOI: 10.1530/acta.0.1130465
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin plasma levels and biological effects following subcutaneous administration of somatostatin in man

Abstract: The rate at which somatostatin appears in the circulation after subcutaneous bolus injection and continuous administration by pump was determined in normal subjects by serial radioimmunoassays of immunoreactive somatostatin. Following a single subcutaneous injection of 250 \g=m\g, the somatostatin peak in plasma appeared after 5 min and had only a transient effect on insulin levels. During continuous administration, somatostatin reached levels able to reduce significantly insulin and glucagon. Somatostatin pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
1989
1989

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The increase in plasma concentration of glycerol after 60 min of surgery in the somatostatin patients may have resulted from the suppression of insulin secretion, as this hormone is a potent inhibitor of lipolysis. A study of the hormonal effects of the subcutaneous injection of somatostatin 250 ug showed a transient reduction in plasma insulin [27]. During a continuous i.v.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in plasma concentration of glycerol after 60 min of surgery in the somatostatin patients may have resulted from the suppression of insulin secretion, as this hormone is a potent inhibitor of lipolysis. A study of the hormonal effects of the subcutaneous injection of somatostatin 250 ug showed a transient reduction in plasma insulin [27]. During a continuous i.v.…”
Section: Discussionmentioning
confidence: 99%